Diglossia Interference in Arabic Language Acquisition: A Study of Indonesian Students at the Indonesian School of Mecca - Chorrin Vitalia Putri; Arif Humaini (Journal of Social Work and Science Education, 2026)
This study examines the interference of ‘Amiyah (colloquial) Arabic in the use of Fuṣḥā (Modern Standard) Arabic among Indonesian diaspora students at the Indonesian School of Mecca, focusing on linguistic manifestations and contributing factors. A descriptive qualitative approach was employed with 16 fourth-grade students selected through purposive sampling. Data were collected via non-participant observation, semi-structured interviews, and documentation. Analysis followed Miles and Huberman’s interactive model integrated with Corder’s Error Analysis framework. Interference manifests in four domains: lexical, phonological, morphosyntactic, and grammatical (nahwu). Six contributing factors were identified: dominance of ‘Amiyah in daily communication, perceived ease of ‘Amiyah, limited Fuṣḥā practice opportunities, structural diglossia differences, foreign language anxiety, and pedagogical factors. This interference contributes to grammatical fossilization, reduced academic vocabulary, code-mixing, pronunciation deviations, and diminished speaking confidence. This study uniquely addresses Arabic diglossia interference within an Indonesian diaspora school context, an underexplored setting in Arabic sociolinguistics and second language acquisition research. Findings recommend sociolinguistically informed instruction incorporating explicit contrastive analysis between Fuṣḥā and ‘Amiyah to mitigate interference and enhance linguistic competence. This research contributes empirical evidence on diglossia interference patterns in diaspora educational contexts, offering actionable insights for curriculum designers and Arabic language educators to develop pedagogical strategies that address the unique challenges faced by learners in Arabic-speaking environments while strengthening Fuṣḥā proficiency.